Relationship between dark triad personality, moral disengagement and cyberbullying among undergraduate student in Universiti Tunku Abdul Rahman - Li, Xin Yan; Hew, Hui Teng; Loh, Shao Heng (2023)
While technology's rapid development grants easy and efficient access to social media platforms, it has also enabled negative consequences like cyberbullying. Therefore, the purpose of the current study was to investigate the relationship between cyberbullying, the dark triad personality, and moral disengagement. In this study, a quantitative cross-sectional design was used, and online questionnaires were adopted to collect data through various social media platforms. Moreover, a purposive sampling method was utilized to collect data from undergraduate students age between 18-24 who study in Universiti Tunku Abdul Rahman and 120 samples involve in this study. The Short Dark Triad Scale (SD3), the 10- item Mechanisms of Moral Disengagement Scale (MMDS-10), and the European Bullying Intervention Project Questionnaire (EBIPQ) were utilized to evaluate the study variables. Then, the collected data was analyzed using IBM SPSS Statistics (SPSS). Pearson’s correlation results concluded that cyberbullying and Machiavellianism have a non-significant and positive relationship, while there is a significant and positive relationship between narcissism and psychopathy towards cyberbullying. In addition, a significant and positive relationship could be found between cyberbullying and moral disengagement. On the other hand, the two variables of narcissism and psychopathy are significantly positively correlated with moral disengagement, while Machiavellianism has a non-significant and positive relationship with moral disengagement. Besides that, the result of multiple linear regression analysis indicated that psychopathy and moral disengagement are the significant predictors of cyberbullying, but not Machiavellianism. Lastly, there has been limited prior research concerning this topic among undergraduate students in the region. Hence, this study aims to fill this research gap within the Malaysian context and serve as a resource to enhance the comprehension of cyberbullying predictors.